Doses de fósforo e zinco na cultura do feijão-caupi - Rosal, Carlota Joaquina de Sousa [UNESP] (2013)
The cowpea is an important socioeconomically legume to the North and Northeast of Brazil, thus becoming an excellent source of protein for feeding of the population. Grain yield is influenced by several factors, in particular the inadequate fertilization. This field experiment was conducted with the objective for evaluating on a in out the effects field conditions, to evaluating the combined effects of phosphorus (P) and zinc (Zn), fertilization on the plant nutritional status and grain yield of cowpea in dystrophic haplic Plinthosol (3.0 mg dm-3 of P and 0,1 mg dm-3). The experimental design consisted of randomized blocks, with five rates of P (0, 40, 80, 120, and 160 kg ha-1P2O5), and three rates of Zn (0, 1, and 3 kg ha-1 Zn), using as sources the triple superphosphate and zinc sulphate, respectively . The fertilizers were broadcasted in the total area of the plot obtaining the The results show that fertilization with P e Zn increased grain yield, obtaining the maximum grain yield (1648 kg ha-1) with the combination of 125 kg ha-1 P2O5 and 2.6 kg ha-1 Zn. The addition of P and Zn increased the concentrations of these nutrients in the grains. The critical level of phosphorus in soil and leaf are 6.3 mg dm-3 (Mehlich-1) and 2.01 g kg-1, respectively